FRI0304 DEFINITION AND STANDARDIZATION OF INTERSTITIAL LUNG DISEASE ASSESSMENT BY ULTRASOUND: RESULTS FROM A DELPHI PROCESS AND WEB-RELIABILITY EXERCISE BY THE OMERACT ULTRASOUND WORKING GROUP (WG). (June 2019) - Sedie, Andrea Delle; Terslev, Lene; Bruyn, George; Cazenave, Tomás; Chrysidis, Stavros; Diaz, Mario; Carlo, Marco DI; Frigato, Marilena; Gargani, Luna; Gutierrez, Marwin; Hocevar, Alojzija; Iagnocco, Annamaria; et al.
Abstract : Background: Interstitial lung disease (ILD) evaluation is challenging, given the low sensitivity of X-ray and pulmonary function tests, and limited accessibility and radiation linked to repetitive HRCT. Lung Ultrasound (US) has shown potential in the evaluation of ILD of autoimmune diseases including systemic sclerosis. Objectives: To define and asses the reliability of definitions of US-detected findings in ILD. Methods: A taskforce (TF) within the OMERACT US WG performed a literature review (LR) to identify US lesions in ILD, a Delphi exercise to define these lesions and a web-based exercise to test the reliability of these definitions by using either intraclass correlation coefficient (ICC) or kappa statistics. Prior to the Delphi exercise all participants received training files and were subsequently asked to provide clips on BL, PLI and normal findings. Based on the results of the LR, which identified B-lines (BL) and pleural line irregularity (PLI) as main US findings in ILD, the Delphi exercise contained statements on US definitions on BL and PLI. After reaching agreement (> 75%) on the above mentioned items, a set of 80 high-quality clips (30 for PLI, 50 for BL), was selected and distributed to the TF members in order to score them (semiquantitatively, 0-2 for PLI and total number for BL) Results: The 3 Delphi rounds and the web-based exercise were completed by 24 and 22 sonographers, respectively. Final definitions are reported in Table I. The web-based exercise showed moderate inter-reader reliability for both BL (ICC=0.61) and PLI (kappa=0.69). Table I: definitions of PLI and BL Pleural line irregularity (PLI ) : a loss of regularity that may be associated with an increase in thickness, focal, diffuse, or nodular B-line (BL ) : a vertical hyperechoic reverberation artifacts that arise from the pleural line, extend to the bottom of the screen without fading, and move synchronously with lung sliding Conclusion: US is a candidate imaging modality to identify and monitor ILD in rheumatic diseases; US consensus based definitions of main US findings were defined and endorsed. Further development is planned for validating US as an outcome measurement instrument for ILD. Disclosure of Interests: Andrea Delle Sedie Speakers bureau: Abbvie, UCB, Celgene, MSD, Lene Terslev Speakers bureau: Speakers fee from : Roche, Novartis, Pfizer, MSD, BMS, Celgene, George Bruyn : None declared, Tomás Cazenave: None declared, stavros chrysidis: None declared, Mario Diaz: None declared, Marco Di Carlo: None declared, Marilena Frigato: None declared, Luna Gargani: None declared, Marwin Gutierrez: None declared, ALOJZIJA HOCEVAR: None declared, Annamaria Iagnocco: None declared, Aaron Juche: None declared, Peter Mandl: None declared, Esperanza Naredo Consultant for: Abbvie, Speakers bureau: AbbVie, Roche, Bristol-Myers Squibb, Pfizer, UCB, Lilly, Novartis, Janssen, and Celgene GmbH, Mohammed A Mortada: None declared, Carlos Pineda: None declared, Francesco Porta: None declared, Viviana Ravagnani: None declared, Carlo Alberto Scirè: None declared, Teodora Serban: None declared, Kate Smith: None declared, Maria Stoenoiu Grant/research support from: Abbvie, Roche, Wyeth, Marika Tardella: None declared, Karina Torralba: None declared, Richard Wakefield: None declared, Maria-Antonietta d'Agostino: None declared